The handbook of research on entrepreneurship in agriculture and rural development - Alsos, Gry Agnete; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar Pub., 2011)
The agriculture sector around the world has experienced profound changes in recent years. This unique and path-breaking Handbook draws together the best current research in the area of entrepreneurship in agriculture, food production and rural development.
pt. 1. Entrepreneurship in the farming sector -- pt. 2. Innovations in food production and distribution -- pt. 3. Agricultural entrepreneurship and its spatial context.
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects -- Handbooks, manuals, etc; Rural development -- Economic aspects -- Handbooks, manuals, etc; Entrepreneurship -- Handbooks, manuals, etc; Agricultural industries -- Handbooks, manuals, etc; Electronic books